The role of three-dimensional reconstructions in understanding the intersegmental plane: an anatomical study of segment 6. (1st May 2020) - Sarsam, Matthieu; Glorion, Matthieu; de Wolf, Julien; Cassiano, Francesco; Puyo, Philippe; Sage, Edouard; Chapelier, Alain
Abstract: OBJECTIVES: The identification of the intersegmental plane during lung segmentectomies remains a practical difficulty, notably with minimally invasive approaches. The intraoperative techniques are based on demarcating either the bronchial or the vascular territories. The goal of this study was to evaluate the use of 3-dimensional reconstructions in understanding the intersegmental plane of segment 6. METHODS: Between March and September 2018, Synapse 3-dimensional programme was used to carry out bilateral venous, arterial and bronchial segmentations of segment 6. All computed tomography (CT) scans were contrast-enhanced and of a high resolution (0.6 mm slices). The patients had normal results on respiratory function tests. The volumes obtained from each of the 3 modalities were then compared. The results are presented as mean and standard deviation and as median and interquartile ranges for lung volume measurements. RESULTS: During the aforementioned period, 15 high-resolution chest CT scans were selected (8 men and 7 women). The median age was 70 years. In all of the studied segments ( N  = 30, 15 right S6 and 15 left S6), the segmental volume of the vein was greater than the segmental volumes of the bronchus and the artery. A significant difference was found between the segmental volumes obtained from the 3 modalities ( P  = 0.001). The segmental volume of the vein was significantly higher than the segmental volume of the bronchus ( P  < 0.001) and the segmental volume of the artery ( P  < 0.001). On the other hand, the segmental volume of the artery was significantly higher than the segmental volume of the bronchus ( P  = 0.01). CONCLUSIONS: Within the limits of this study, the segmental venous volume of S6 was greater than the volumes of the segmental bronchial and arterial volumes. Thus, depending solely on bronchial techniques might lead to leaving a border zone in venous congestion.